An Information Systems Study on the Supply and Property Management Office Utilization Section - Aliga, Alma R.; Guevara, Ma. Paz S.; Potenciano, Joan Mary S.; Senar, Racquel S. (Diliman, Quezon City College of Engineering, 1993)
The Supply and Property Management Office (SPMO) of the University of the Philippines in Diliman, Quezon City, acts as the central procurement, inventory control and disposal office for the UP Diliman units and extensions in UP San Fernando and Baguio. It is located at the basement of Quezon Hall, and was called the Property Office before the reorganization in 1983. Currently, almost thirty people are employed by this office. The SPMO is composed of the Procurement, Utilization and Disposal Sections, headed by their respective chiefs. In summary, the Procurement Section is responsible for the acquisition of equipment and supplies; the Utilization Section manages the inventory and inspection of the goods upon arrival and while in storage; the Disposal Section handles the equipment after the request for condemnation and elimination or sale of scrap. Because of the heavy exchange of data involved in this office and its plans for eventual computerization of data storage, this site is ideal for an information study. Although a comprehensive report on all three sections would be ideal, it would require more time than allotted for the study. Thus, only the Utilization Section will be the subject of this report. Moreover, due to the pending change of inventory record-keeping from a manual system to a computerized system, this study will be able to evaluate the merits of the proposal and further improve it.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: Supply and Property Management Office (SPMO) of the University of the Philippines in Diliman, Quezon City; Government property; Government purchasing; Inventory control; Information resources management